Iron house - Hart, John, 1965- (Thomas Dunne Books/St. Martin's Press, 2011)
There was nothing but time at Iron House. Time to burn, time to kill, and time for Michael to emerge strong and unforgiving while his brother, Julian, became a tormented soul at the orphanage for boys. Two decades later Michael returns to North Carolina with a sentence on his head, the mob in hot pursuit, and his disturbed brother in trouble of a different kind. One man is destined to break the chains of his fate.